Index to the Legon Observer Volumes Two through Nine, 1967-1974 - Dadson, T. (The Legan Society on National Affairs, 1979)
The Legon Observer was published from July 1966 until July 1974 when it ceased publication . (A special statement was issued as explanation of the cessation in October 1974.) During this period, the journal was the leading organ of social, economic and political commentary in Ghana. In 1971, The Legon Society on National Affairs published an index to volume one. The present index covers the contents of volumes two to nine, and thus completes the indexing of all the issues of Legan Observer ever published. To ensure uniformity the arrangement of the earlier index has been followed as far as possible . Hore subject headings and form headings have been added
Journal
Keywords: Observer; Legon